Education for Sustainability: Innovative Teaching on Photosynthesis of Aquatic Plants in Ecological Context - Ryplova, Renata; Pokorny, Jan; Baxa, Marek (European Journal of Sustainable Development, 2023)
Eutrophication due to high load of nutrients from the catchment is significant worldwide problem causing impairment of water ecosystems and water quality. The reason is tight connection of eutrophication with photosynthetic biomass production of blue green algae resulting in extreme changes of oxygen level, anoxia at the bottom and release of toxic substances in water. Acceleration and extension of eutrophication due to human activities together with insufficient human understanding of the ecological role of photosynthesis of aquatic plants leads to inappropriate water and landscape management resulting in further loss of clear water. To save enough clear water supplies for future generation it is necessary to improve human understanding of these processes starting already from school education. This contribution brings results of a survey aimed on the impact of developed innovative teaching activity on photosynthetic biomass production of aquatic plants in ecological context and using digital technologies which was implemented into the education at Czech upper secondary schools. Significant improvement of student understanding of ecological function of photosynthetic biomass production in water and increase of attractiveness of plant education for students were proved. The contribution of innovative teaching on photosynthetic biomass production in ecological context for sustainable education is discussed. Keywords: Plant blindness, Aquatic plants, Eutrophication, Sustainable Education, Water.